A Study of Disposition, Engagement, Efficacy, and Vitality of Teachers in Designing Science, Technology, Engineering, and Mathematics Education - Lin, Pei-Yi; Chai, Ching Sing; Jong, Morris Siu-Yung (Frontiers in Psychology, 2021)
The present work proposed and tested a theoretical model of how teachers’ perceptions of disposition, engagement, and efficacy for science, technology, engineering, and mathematics (STEM) e-learning can predict their sense of vitality when they designed STEM education. Upon the proposition, we developed and validated an instrument for examining the relationships between these variables. The participants were 122 secondary teachers of STEM education in Hong Kong. The instrument included four design aspects: (i) disposition, (ii) lesson design engagement, (iii) efficacy for designing STEM e-learning, and (iv) teachers’ vitality after attending a series of STEM professional development activities. To analyze the relationships among the variables, partial least squares–structural equation modeling was employed. The teachers’ disposition predicted lesson design engagement, and both predicted efficacy for designing STEM e-learning. In other words, if teachers have high proposition toward designing learning activities, their engagement in the lesson design process may enhance their capacities in designing and implementing such activities. Also, teachers’ disposition and lesson design engagement predicted their vitality, revealing that well-suited STEM teachers should not only be able to design a STEM curriculum but should also have a positive perception of STEM education.